Evaluation of Lotion Formulation Using Salam Leaf Extract (Syzygium polyanthum) with Antioxidant Activity - Ambarita, Petrus Alvin Peter; Veni Putri Nurhayati; Tia Azzahra Putri; Tifani Pardede; Shefia Dhiya Khansa; Herayati (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Bay leaves (Syzygium polyanthum) contain active compounds such as tannins, saponins, flavonoids, and steroids, which offer various benefits in skincare, including antioxidant, antimicrobial, anti-inflammatory, and natural cleansing properties. This study aimed to evaluate the antioxidant activity of bay leaf extract and assess the quality of lotion formulation containing the extract. Extraction was carried out using the maceration method with 70% ethanol as the solvent, and antioxidant activity was tested using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, yielding an IC50 value of 48.64 ppm, indicating moderate antioxidant activity. The lotion formulations were evaluated for organoleptic properties, homogeneity, pH, spreadability, viscosity, and emulsion stability. Results showed that formula F2 had superior quality compared to F1, with a spreadability of 6.5 cm (compliant with SNI 16-3499-1996), pH 6.70 (safe range 4.5–8), creamier texture, lower stickiness and greasiness, and faster absorption time (30 seconds). Formula F2 also demonstrated ideal viscosity (6805 mPaS) and shear thinning properties (torQ 68.1%), which ease application on the skin. Based on these findings, formula F2 meets the requirements for topical cosmetics according to SNI and the Indonesian Pharmacopoeia VI edition, especially in terms of pH, physical stability, and viscosity, and thus shows promising potential for development as a natural-based cosmetic product that is both safe and effective in protecting the skin from free radicals and irritation.